Metagenomic Insights Into Functional and Taxonomic Compositions of an Activated Sludge Microbial Community Treating Leachate of a Completed Landfill: A Pathway-Based Analysis - Yasuda, Shohei; Suenaga, Toshikazu; Orschler, Laura; Agrawal, Shelesh; Lackner, Susanne; Terada, Akihiko (Frontiers in Microbiology, 2021)
Upcycling wastes into valuable products by mixed microbial communities has recently received considerable attention. Sustainable production of high-value substances from one-carbon (C1) compounds, e.g., methanol supplemented as an external electron donor in bioreactors for wastewater treatment, is a promising application of upcycling. This study undertook a gene-centric approach to screen valuable production potentials from mixed culture biomass, removing organic carbon and nitrogen from landfill leachate. To this end, the microbial community of the activated sludge from a landfill leachate treatment plant and its metabolic potential for the production of seven valuable products were investigated. The DNA extracted from the activated sludge was subjected to shotgun metagenome sequencing to analyze the microbial taxonomy and functions associated with producing the seven products. The functional analysis confirmed that the activated sludge could produce six of the valuable products, ectoine, polyhydroxybutyrate (PHB), zeaxanthin, astaxanthin, acetoin, and 2,3-butanediol. Quantification of the detected functional gene hit numbers for these valuable products as a primary trial identified a potential rate-limiting metabolic pathway, e.g., conversion of L-2,4-diaminobutyrate into N-γ-acetyl-L2,4,-diaminobutyrate during the ectoine biosynthesis. Overall, this study demonstrated that primary screening by the proposed gene-centric approach can be used to evaluate the potential for the production of valuable products using mixed culture or single microbe in engineered systems. The proposed approach can be expanded to sites where water purification is highly required, but resource recovery or upcycling has not been implemented.